Video game acceptance : a meta-analysis of the extended technology acceptance model - Wang, Xiaohui (2020)
The current study systematically reviews and summarizes the existing literature of game acceptance, identifies the core determinants, and evaluates the strength of the relationships in the extended technology acceptance model. Moreover, this study segments video games into two categories: hedonic and utilitarian and examines player acceptance of these two types separately. Through a meta-analysis of 50 articles, we find that perceived ease of use (PEOU), perceived usefulness (PU), and perceived enjoyment (PE) significantly associate with attitude and behavioral intention. PE is the dominant predictor of hedonic game acceptance, while PEOU and PU are the main determinants of utilitarian game acceptance. Furthermore, we find that respondent type and game platform are significant moderators. Findings of this study provide critical insights into the phenomenon of game acceptance and suggest directions for future research.